Measuring financial toxicity as a clinically relevant patient‐reported outcome: The validation of the COmprehensive Score for financial Toxicity (COST). Issue 3 (7th October 2016) - de Souza, Jonas A.; Yap, Bonnie J.; Wroblewski, Kristen; Blinder, Victoria; Araújo, Fabiana S.; Hlubocky, Fay J.; Nicholas, Lauren H.; O'Connor, Jeremy M.; Brockstein, Bruce; Ratain, Mark J.; Daugherty, Christopher K.; Cella, David
Abstract : BACKGROUND: Cancer and its treatment lead to increased financial distress for patients. To the authors' knowledge, to date, no standardized patient‐reported outcome measure has been validated to assess this distress. METHODS: Patients with AJCC Stage IV solid tumors receiving chemotherapy for at least 2 months were recruited. Financial toxicity was measured by the COmprehensive Score for financial Toxicity (COST) measure. The authors collected data regarding patient characteristics, clinical trial participation, health care use, willingness to discuss costs, psychological distress (Brief Profile of Mood States [POMS]), and health‐related quality of life (HRQOL) as measured by the Functional Assessment of Cancer Therapy: General (FACT‐G) and the European Organization for Research and Treatment of Cancer (EORTC) QOL questionnaires. Test‐retest reliability, internal consistency, and validity of the COST measure were assessed using standard‐scale construction techniques. Associations between the resulting factors and other variables were assessed using multivariable analyses. RESULTS: A total of 375 patients with advanced cancer were approached, 233 of whom (62.1%) agreed to participate. The COST measure demonstrated high internal consistency and test‐retest reliability. Factor analyses revealed a coherent, single, latent variable (financial toxicity). COST values were found to be correlated with income (correlation coefficient [r] = 0.28; P <.001), psychosocial distress (r = ‐0.26; P <.001), and HRQOL, as measured by the FACT‐G (r = 0.42; P <.001) and by the EORTC QOL instruments (r = 0.33; P <.001). Independent factors found to be associated with financial toxicity were race ( P  = .04), employment status ( P <.001), income ( P  = .003), number of inpatient admissions ( P  = .01), and psychological distress ( P  = .003). Willingness to discuss costs was not found to be associated with the degree of financial distress ( P  = .49). CONCLUSIONS: The COST measure demonstrated reliability and validity in measuring financial toxicity. Its correlation with HRQOL indicates that financial toxicity is a clinically relevant patient‐centered outcome. Cancer 2017;123:476–484. © 2016 American Cancer Society . Abstract : The COmprehensive Score for financial Toxicity (COST) is validated in a novel sample of patients with cancer. Independent factors found to be associated with financial toxicity include race, employment, income, number of inpatient admissions, and psychological distress.